Benefits of adding forestry clearance residues for the soil and vegetation of a Mediterranean mountain forest. - Hueso-González, Paloma; Martínez-Murillo, Juan Francisco; Ruiz-Sinoga, José Damián (Elsevier, 2018)
Desertification is occurring throughout the mountainous areas of the Mediterranean. These processes lead to reduced soil fertility, increased soil loss, and reduced vegetation cover and species richness. To prevent further damage, it is recommendable to use low-cost approaches that are compatible with the European Strategy of Circular Economy guidelines. We investigated the systemic benefits from recycling of forest clearance residue by adding it to a dry Mediterranean mountainous area. More specifically, we performed afforestation without addition of residue in two control plots (C plots), and afforestation with addition of 10 Mg ha− 1 of clearance residue from a nearby region dominated by Aleppo pine (Pinus halepensis Mill.) in two other plots (PM plots). We conducted the experiments throughout 30 months after the afforestation process. Eighteen months after the intervention, the PM plots had significant increases in the soil organic carbon (SOC), and related increases in ecosystem productivity and stability. More generally, addition of clearance residues improved soil and vegetation recovery, and contributed to more successful afforestation. The improvements may be explained by an increase of infiltration process due to the physical changes in the soil following bio-waste addition. Addition of the forest residues increased the formation of soil macrochannels, and also increased the sink area, thereby improving the hydrodynamics of the ecosystem. Thus, soil loss was reduced by 98.2% in the PM plots relative to the C plots. Our study indicates that application of forest clearance residues to Mediterranean mountainous areas is an effective land management practice that produces very little waste, and it is in accordance with European policy.
https://v2.sherpa.ac.uk/id/publication/15487
Keywords: Suelos - Conservación; Circular economy; Soil amendments